Use of Arduino in Primary Education: A Systematic Review - Pedro Antonio García-Tudela; José-Antonio (MDPI AG, 2023)
In the last two decades, technological advances have been spectacular, and their transcendence has touched all areas of society. Specifically, in the field of education, these advances have allowed projects and approaches such as computational thinking to be taken up more strongly through interdisciplinary visions such as the STEM subjects and technological devices such as Arduino. The main objective of this article is to analyse the uses of Arduino and the achievements it has attained at primary-education level. To this end, a systematic review was carried out in the SCOPUS and Web of Science databases. The methodology used was the PRISMA statement and the SALSA framework. In accordance with the exclusion criteria applied, nine scientific papers from the last seven years were obtained. The qualitative software ATLAS.ti was used to extract the results. These papers reveal that the most commonly used methodology for incorporating the Arduino board into teaching is problem based learning (PBL) in the context of STEM subjects. In addition, programming environments, such as Scratch, and other electronic components have been used, which have enabled the development of computational thinking and the acquisition of technological knowledge, among other achievements.